GHG Emission and Cost Performance of Life Cycle Energy on Agricultural Land Used for Photovoltaic Power Plant - Thanarak, Prapita; Chiramakara, Teerarat (International Journal of Energy Economics and Policy, 2019)
The research aims to analyze land use from agricultural land for photovoltaic power plant construction and electricity generation. Geographic information system technology was used to analyze and decide the suitability of the land for a photovoltaic power plant. GHG assessment and life cycle cost were applied in this study which covered 4 processes: land preparation, logistics, construction and system installment, and electrical generation. The research found that the maps showed the area to be moderately abundant clay, outside the irrigated area, the average rainfall was 1,100 mm./year and agriculture is only possible four months per year. The average solar irradiance was 17.6 W/m2.d for this area which is suitable for building a photovoltaic power plant. CO2 emissions for land preparation, transportation, construction and electrical generation were 0.148tCO2eq/kWh, 0.196 tCO2eq/kWh, 0.418 tCO2eq/kWh and 6.932tCO2eq/kWh, respectively and the net CO2 emission was -0.549 kgCO2eq/kWh. Life cycle cost for 25years is 169.79million baht and the cost of energy is 4.12 baht/kWh. The empirical results show that land use assessment of agriculture for the photovoltaic power plant was appropriate and worth wile without affecting the environment and economy. Keywords: Greenhouse gas, geographic information system, land use, life cycle cost, photovoltaic power plant. JEL Classifications: C8, G0, M2 DOI: https://doi.org/10.32479/ijeep.7394